Nurse Readiness in Disaster Preparedness During Pandemic Covid-19 - Putra Agina Widyaswara Suwaryo; Sarwono Sarwono; Hendri Tamara Yuda (Proceedings Series on Health & Medical Sciences, 2021)
Nurses have a role to take part in disaster situations. The development of a theoretical for disaster nursing is very much needed, but there are not many articles that discuss disaster nursing. This can happen because the nature of disasters experienced by humans cannot be predicted when they will occur and Health professionals need to concentrate on these activities. There have not been many in-depth studies related to how prepared nurses are in dealing with disasters, given their important role, especially in providing physical and psychological handling and assistance to victims when a disaster occurs. The COVID-19 pandemic situation as it is now is also a challenge for health workers, especially nurses. This study was conducted to determine the relationship between knowledge and nurse readiness in disaster preparedness through the 8 dimensions contained in the Emergency Preparedness Information Questionnaire (EPIQ) for nurse readiness in disaster preparedness, and 40 questionnaires for knowledge about disasters. The sample is a nurse in a hospital, active in disaster activities, aged 21-60 years, and willing to become research respondents. The total number of nurses is 66 people. The data collection technique was carried out on all nurses who worked and were active in disaster activities at the PKU Muhammadiyah Hospital in Kebumen. Data was taken through an online recap and analyzed using SPSS 25. The results showed average knowledge is 61.4 with Std Dev 12.97 (38-88) and Nurse readiness 76.4 with Std Dev 6.62 (61-89). The results of the Pearson correlation test showed that there was a relationship between knowledge and nurse readiness in disaster preparedness (p = 0.000). Massive and continuous education process will improve nurses' preparedness in dealing with the COVID-19 disaster